Synergies Between Monetary and Macroprudential Policies in Thailand - Fukunaga, Ichiro (IMF Working Papers; Working Paper ;, 2020)
A dynamic stochastic general equilibrium (DSGE) model tailored to the Thai economy is used to explore the performance of alternative monetary and macroprudential policy rules when faced with shocks that directly impact the financial cycle. In this context, the model shows that a monetary policy focused on its traditional inflation and output objectives accompanied by a well targeted counter-cyclical macroprudential policy yields better macroeconomic outcomes than a lean-against-the-wind monetary policy rule under a wide range of assumptions.